Programmed Intermittent Epidural Bolus in Comparison with Continuous Epidural Infusion for Uterine Contraction Pain Relief After Cesarean Section: A Randomized, Double-Blind Clinical Trial - Mo X; Zhao T; Chen J; Li X; Liu J; Xu C; Song X (Dove Medical Press, 2022)
Xiaofei Mo,1 Tianyun Zhao,1 Jinghui Chen,1 Xiang Li,1 Jun Liu,2 Cuiyi Xu,1 Xingrong Song1 1Department of Anesthesiology, Guangzhou Women and Children's Medical Center, Guangzhou Medical University, Guangzhou, People's Republic of China; 2Department of Medical Records, The Sixth Affiliated Hospital, Sun Yat-Sen University, Guangzhou, People's Republic of ChinaCorrespondence: Xingrong Song; Tianyun Zhao, Department of Anesthesiology, Guangzhou Women and Children's Medical Center, Guangzhou Medical University, 9 Jinsui Road, Tianhe District, Guangzhou, 510623, People's Republic of China, Tel +86 13922416303 ; +86 18198907639, Fax +86 20 38076243, Email sxjess@163.com; wenyan_404@tom.comPurpose: Programmed intermittent epidural bolus (PIEB) was reported to provide superior maintenance of labour analgesia with better pain relief and less motor block than continuous epidural infusion (CEI). Whether this is also evident for uterine contraction pain relief after cesarean section remains unknown.Patients and Methods: Parturients scheduled for cesarean section were recruited for the study. At the end of the surgery, after a similar epidural loading dose given, patients received either PIEB (6 mL·h− 1) or CEI (6 mL·h− 1) of 0.1% ropivacaine. The primary outcome was the uterine contraction pain assessed with visual analog scale (VAS-U) at the postoperative 36 h. Secondary outcomes included incision pain at the rest (VAS-R) and in the movement-evoked (VAS-P), and lower extremity motor block (defined as Bromage score > 0). The whole profile of VAS scores between groups was analyzed using linear mixed model. When significant differences were found, the pairwise comparison was done with the Mann Whitney U-test followed by Bonferroni correction.Results: One hundred and twenty parturients were studied (PIEB, 60; CEI, 60). VAS-U at the postoperative 36 h in the PIEB group was lower than in the CEI group (Bonferroni-adjusted P < 0.01). The linear mixed model indicated that VAS-U, VAS-R and VAS-P were lower in the PIEB group compared with the CEI group (all P < 0.01). Motor block was higher in the CEI group than in the PIEB group during the study period except 2 h (all P < 0.05). No differences of adverse events such as hypotension and urinary retention were observed between the two groups.Conclusion: Programmed intermittent epidural bolus provides more effective uterine contraction and incision pain relief and less motor block after cesarean section than continuous epidural infusion without an increased risk of urinary retention and blood pressure instability.Keywords: cesarean section, epidural, pain, postoperative analgesia, uterine contraction